The Experimental Validation of an Electromechanical Dynamic Model of a Piezoelectric Bimorph Beam for Prediction of Power Generation - Lumentut, Mikail; Howard, Ian (Engineers Australia, 2010)
The extraction of usable electrical power from vibration environments has attracted recent interest from many researchers because of the potential benefit for recharging batteries and for powering wireless sensor nodes. In this paper, we present a comparison of experimental and analytical predictions of power generation of a piezoelectric bimorph beam with a tip mass under dynamic base excitations. The strain fields in the interlayer bimorph elements can be considered to have been created due to the transverse bending moment and longitudinal force resulting from the input base excitations. In such a situation, the mechanical domain can also affect the physical behaviour of the polarity and electric field of the bimorph creating the resulting electrical charge and potential. The coupling field effect of the electromechanical dynamic system generates the resulting electrical potential and power resulting in the benefit of self-power storage. The piezoelectric bimorph beam was modelled using the Euler-Bernoulli’s beam assumptions. In this case, the constitutive electromechanical dynamic equations were derived analytically based on the weak form of the Hamiltonian principle.As a result, the relationships of the frequency response functions (FRF) between the multi-input from mechanical forms and multi-output from mechanical and electrical forms can be obtained according to the Laplace transformation. In this case, the comparisons and validations were achieved by comparing the results obtained from the theoretical models and the experimental results.